Hubungan Faktor Persepsi Mahasiswa Dalam Pengelolaan Ruang Rawat Inap Terhadap Kepuasan Mahasiswa Dalam Praktek Klinik Keperawatan Di RSUD Pariaman: The Relationship between Student Perception Factors in Inpatient Room Management Student Satisfaction in Nursing Clinical Practice at the Regional Hospital Pariaman - Mechi Silvia Dora; Dini Qurata Ayuni (Fakultas Keperawatan Universitas Andalas, 2020)
The success of students in clinical nursing practice is largely determined how the inpatient room management is perceived by students as a form of experience required. The purpose of this study was to analyze the effect of student perception factors in the management of inpatient rooms on student satisfaction in nursing clinical practice. This type of research is observational with quantitative analysis methods. The design of this study is a cross sectional study. The results of the bivariate analysis showed that there was a correlation between students' perceptions about clinical leadership. leadership (p-value 0.003), supervision of the head of the room (p-value 0.042), coordination between practice supervisors (p-value 0.032), and practical work environment (p-value 0.033) with student satisfaction in nursing clinical practice. The results of multivariate analysis showed that the most influential effect on student satisfaction in nursing clinical practice was about clinical leadership leadership (p-value 0.012 <0.05 and Exp (B) 3.436) and work environment (p-value 0.010 <0.05 and Exp ( B) 2,285) on student satisfaction in clinical nursing practice. There is an influence together with students' perceptions about clinical leadership and work environment leadership on student satisfaction in clinical nursing practice. Improving clinical supervisors skills in the form of providing direct assessment when nursing actions, increasing openness and being able to provide confidence to students to be able to carry out nursing action procedures